The Impact Grit and Achievement Goal Orientation have on Athletic Training Students' Persistence - Hannah Harner; Kimberly Peer; Chris Moser; John Cindric (Bowling Green State University, 2021)
Purpose: Athletic training education continues to evolve thereby increasing the importance of student retention. Understanding student motivation through achievement goal orientation and grit scores may help support student's persistence in an athletic training program. The purpose was to determine if a relationship exists between achievement goal orientation and grit to help provide educators a better understanding of their students' reasons for persisting to help improve retention. Methods: An achievement goal orientation survey and grit scale were administered, and quantitative data was analyzed statistically from Commission on Accreditation of Athletic Training Education- accredited programs in good standing for the 2018-2019 academic year. Results: A total of 520 professional athletic training students participated. There was a significant main effect (F(1,3)=690.0, pConclusions: Athletic training students have similar grit scores across all cohorts and classify higher with mastery goal orientation compared to performance-approach, performance-avoidant, and work-avoidant orientations. Educators should understand students' motivation to provide support and challenging tasks for their passion and perseverance for athletic training. Key Words: grit, mastery, performance-approach, performance-avoidant, work-avoidant.